Uncovering paradoxes of compassion at work: a dyadic study of compassionate leader behavior - Krause, Vinzenz; Rousset, Célia; Schäfer, Björn (Frontiers in Psychology, 2023)
In today’s business world, organizations tend to overlook that employees face suffering caused by work and non-work-related events that can negatively impact business organizations in the long run. One way to address this challenge is through leadership acknowledging and alleviating employees’ suffering to ensure a company’s success. However, research on compassion and leadership in business settings is still relatively scarce. In this study, we aim to extend the organizational compassion literature by addressing our research question: “What are paradoxes induced by compassionate leader behavior in the workplace in the context of social hierarchy?”. We conducted a qualitative exploratory study based on 12 semi-structured interviews with six dyads of leaders and their direct subordinates from small, medium, and large firms representing different industries. The findings of our study indicate that compassionate leader behavior goes hand-in-hand with paradoxical situations that both leader and member face in the workplace, supporting the proposition that compassion as a social, interpersonal process is complex and multi-faceted. Our analysis identified 6 compassion paradoxes that spring from compassion from a leader towards a member. Our study differentiates from other research of compassion paradoxes in the sense that it also focuses on the interplay between leader and member. From that perspective, the findings of our study indicate that social hierarchy is playing a crucial role and exacerbating some paradoxical tensions. This consideration implies that to be effective, compassionate leaders need to have or develop the ability to continuously transcend those compassion paradoxes, as well as support their members in transcending the paradoxes they find themselves dealing with. Thus, the findings of our study contribute to management literature in the field of Positive Organizational Scholarship (POS) by highlighting compassion as a critical element of dyadic leader-subordinate relationships that could be reinforced by systematically building more competence in leaders and members to navigate the tensions emerging from the identified compassion paradoxes. Additionally, we provide limitations and recommendations for further research, along with several theoretical and practical implications of the results, which are particularly relevant for practitioners such as managing directors, leaders, employees, human resource managers, academics, and business and HR consultants.